2020
DOI: 10.1051/0004-6361/202038393
|View full text |Cite
|
Sign up to set email alerts
|

Progenitor properties of type II supernovae: fitting to hydrodynamical models using Markov chain Monte Carlo methods

Abstract: Context. The progenitor and explosion properties of type II supernovae (SNe II) are fundamental to understanding the evolution of massive stars. Particular attention has been paid to the initial masses of their progenitors, but despite the efforts made, the range of initial masses is still uncertain. Direct imaging of progenitors in pre-explosion archival images suggests an upper initial mass cutoff of ∼18 M⊙. However, this is in tension with previous studies in which progenitor masses inferred by light-curve … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
6

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 94 publications
2
35
0
6
Order By: Relevance
“…where L * (t (Martinez et al 2020). We implemented several minimization approaches and found that the above method worked best for the current work.…”
Section: Light Curve Fittingmentioning
confidence: 99%
“…where L * (t (Martinez et al 2020). We implemented several minimization approaches and found that the above method worked best for the current work.…”
Section: Light Curve Fittingmentioning
confidence: 99%
“…We also compared the semi-analytic fitting results from Jäger et al (2020) to hydrodynamical modelling results from Martinez et al (2020), and found that the estimated ejecta masses are similar. For SN 2005cs, the best-fit ejecta mass with the analytic model is 8.84 M , which is similar to the hydrodynamical result of 8 M .…”
Section: Appendix A: Diluted Blackbody Fitmentioning
confidence: 94%
“…However, some discrepancies appear around ≈ 25 days where the observations show a slightly higher luminosity than the model. Finally, we note that, although we have not considered the photospheric velocity evolution in the modelling (which could lead to a possible degeneracy in the parameters found, see discussion in Martinez et al 2020 and references therein), the model gives a relatively good representation of the Fe λ5169 velocities as shown in the bottom panel of Figure 8.…”
Section: Double 56 Ni Distributionmentioning
confidence: 99%